2018
DOI: 10.1016/s2215-0366(18)30224-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between attention deficit hyperactivity disorder and asthma: a systematic review and meta-analysis and a Swedish population-based study

Abstract: Swedish Research Council and Shire International GmbH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 39 publications
9
106
2
2
Order By: Relevance
“…In ADHD, asthma and obesity are increased. 16,17 Risk of asthma is also increased in autism. 18 In bulimia, there is a marked increase in risk of diabetes (OR 3.45) and in anorexia, the risk is significantly decreased (OR 0.71).…”
Section: Other Mental Disordersmentioning
confidence: 99%
“…In ADHD, asthma and obesity are increased. 16,17 Risk of asthma is also increased in autism. 18 In bulimia, there is a marked increase in risk of diabetes (OR 3.45) and in anorexia, the risk is significantly decreased (OR 0.71).…”
Section: Other Mental Disordersmentioning
confidence: 99%
“…Comorbidity with allergic and autoimmune disorders such as atopic eczema, allergic rhinitis and asthma is another factor that could increase the risk for ADHD and future research may lead to a better understanding of the mechanisms underlying the observed comorbidity [38,[42][43][44]. In a meta-analysis and a large-scale genome-wide association study (GWAS), associations between asthma and ADHD were found in both children and adults [45,46]. Also, patients with ADHD and asthma had similar brain region dysfunctions and higher levels of cytokines and IgE compared to healthy children, resulting in alterations to the regions in the brain associated with emotional and behavioural control [38,42,47].…”
Section: Inflammation and The Relationship With Adhdmentioning
confidence: 99%
“…For the years of parents going out and the grades of left-behind children, r was calculated by the same method, using two groups at both ends because they are continuous variables. We use Cohen's guidance to explain the effect size, where r is at least 0.10 = small, 0.30 = medium, and 0.50 = large (Cairns, Yap, Pilkington, & Jorm, 2014;Cohen, 1992).Because of the heterogeneity among the studies, we use the random effect model to analyse the data (Cortese et al, 2018). I 2 was used to assess heterogeneity while Egger test and funnel plots to assess publication bias (Egger, Davey Smith, Schneider, & Minder, 1997;Egger, Smith, & Phillips, 1997).…”
Section: Discussionmentioning
confidence: 99%